Effects of extrusion parameters on physicochemical properties of flaxseed snack and process optimization - Min, Wu; Yi, Liu; Lijun, Wang; Dong, Li; Zhihuai, Mao (International Journal of Agricultural and Biological Engineering, 2015)
In order to optimize the extrusion process of flaxseeds snacks, the influence of different extrusion conditions on flaxseed production were studied by using the general four-factor quadratic designs of rotary combination and response surface methodology (RSM). Four extrusion conditions, the extrusion temperature (100-160°C), screw speed (60-180 r/min), feeding speed (18.35-54.95 kg/h) and moisture content (14%-30% w/w) were used as variables to detect the change of in vitro protein digestibility, expansion index, bulk density and texture (hardness and brittleness) of extruded productions. Through superimposed RSM contour map, it was found that the optimum extrusion conditions could be obtained at feed composition with flaxseed content of 20%, moisture content of 17.37%-22.43%, extrusion temperature of 134.3-156.1°C, screw speed of 114-165.7 r/min and feeding speed of 34.38-45.95 kg/h, respectively. Moreover, the composition and content of fatty acid in flaxseed-maize mixture changed rarely after extruded process, which indicated that extrusion had little impact on fatty acid. Under the optimum extrusion conditions, the flaxseed-maize blends can be extruded into acceptable snack foods.Keywords: flaxseed, extrusion, optimization, physicochemical property, in vitro digestibilityDOI: 10.3965/j.ijabe.20150805.2093Citation: Wu M, Liu Y, Wang L J, Li D, Mao Z H. Effects of extrusion parameters on physicochemical properties of flaxseed snack and process optimization. Int J Agric & Biol Eng, 2015; 8(5): 121－131.